Response assessment using [68Ga]Ga‐PSMA ligand PET in patients undergoing systemic therapy for metastatic castration‐resistant prostate cancer - Grubmüller, Bernhard; Rasul, Sazan; Baltzer, Pascal; Fajkovic, Harun; D'Andrea, David; Berndl, Florian; Maj‐Hes, Agnes; Grubmüller, Karl Hermann; Mitterhauser, Markus; Wadsak, Wolfgang; Pfaff, Sarah; Shariat, Shahrokh F.; et al. (The Prostate, 2020)
Background To assess which parameters of [68Ga]Ga‐PSMA‐11 positron emission tomography (PSMA‐PET) predict response to systemic therapies in metastatic (m) castration‐resistant prostate cancer (CRPC). In addition, to investigate which of these factors are associated with overall survival (OS). Methods We retrospectively assessed the following PSMA‐PET parameters in 43 patients before and after systemic therapies for mCRPC: PSMA total tumor volume (TTV), mean standardized uptake value (SUVmean), SUVmax, and SUVpeak. prostate‐specific antigen (PSA) levels and PSMA‐PET/CT(magnetic resonance imaging [MRI]) imaging were both performed within 8 weeks before and 6 weeks after systemic therapy. PSMA‐PET and CT (MRI) images were reviewed according to the modified PET Response Criteria in Solid Tumors (PERCIST) and Response Evaluation Criteria in Solid Tumors (RECIST) 1.1. Results were compared to PSA response. Univariable survival analyses were performed. Results Overall, 43 patients undergoing 67 systemic therapies were included (9 patients radium‐223, 12 cabazitaxel, 22 docetaxel, 6 abiraterone, and 18 enzalutamide). Median serum PSA level before any therapy was 11.3 ng/mL (interquartile range [IQR] = 3.3, 30.1). Delta (d) PSA after systemic therapies was −41%, dTTV 10.5%, dSUVmean −7.5%, dSUVmax −13.3%, dSUVpeak −12%, and dRECIST −13.3%. Overall, 31 patients had dPSA response (46.3%), 12 stable disease (17.9%), and 24 progressive disease (35.8%). All observed PET parameters, as well as the RECIST evaluation, were significantly associated with PSA response (dTTV P = .003, dSUVmean P = .003, dSUVmax P = .011, dSUVpeak P < 0001, dRECIST P = .012), while RECIST assessment was applicable in 37 out of 67 patients (55.2%). Within a median follow‐up of 33 months (IQR = 26, 38), 10 patients (23.3%) died of PC. On univariable survival analyses, neither the investigated PET parameters nor PSA level or RECIST criteria were associated with OS. Conclusion PSMA‐PET provides reliable parameters for prediction of response to systemic therapies for mCRPC. These parameters, if confirmed, could enhance RECIST criteria, specifically concerning its limitations for sclerotic bone lesions.